The Lasting Benefits of Teams: Tie Vitality After Teams Disband - Maloney, Mary M.; Shah, Priti Pradhan; Zellmer-Bruhn, Mary; Jones, Stephen L. (Organization Science, 2019)
This paper introduces the concept of tie vitality, which indicates the durability and accessibility of team member connections after a team has disbanded as an additional measure of team effectiveness. The authors integrate the team and social network literatures to investigate the effects of team relational capital, team advice density, and dyadic similarities on tie vitality. Two field studies of graduate business student teams show that team relational capital—a psychological team-level state reflecting trust, identification, and mutual obligations among teammates—positively relates to tie vitality. Furthermore, team-level advice network density—a structured behavioral pattern of advice seeking and receiving—amplifies the positive relationship between relational capital and tie vitality. Results also indicate that dyad similarity relates to tie vitality, although it varies depending on which demographic characteristics are considered. Overall, findings indicate that the connections made in teams remain active after teams disband, with the extent of vitality depending on qualities developed during the team experience.